Sosialisasi Arah Kebijakan Bantuan Stimulan Perumahan Swadaya (BSPS) dalam Percepatan Penurunan Kemiskinan Ekstrem Melalui Peningkatan Kualitas Rumah Tidak Layak Huni dan Penanganan Kawasan Perumahan dan Permukiman Kumuh Terintegrasi - Seri Mughni Sulubara; T. Saiful Basri; Zulfa Zainuddin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This community service was carried out for the community in Negeri Antara and Pancar Jelobok Villages, Pintu Rime Gayo District, Bener Meriah Regency. The problems faced are the poverty level and the quality of uninhabitable houses (RTLH) for low-income people (MBR). The research objective is to provide socialization of self-help housing stimulant assistance (BSPS) in overcoming poverty levels and improving the quality of uninhabitable houses and handling integrated housing and slum areas. The method used is descriptive research with a qualitative approach with a sampling technique that uses purposive sampling technique. The results of the research are that the people of Negeri Antara and Pancar Jelobok Villages, Pintu Rime Gayo District, Bener Meriah Regency are very enthusiastic and feel helped by the existence of Self-Help Housing Stimulant Assistance (BSPS) so that they are provoked/motivated to make livable houses with the assistance provided by the government.